Productivity Deceleration when Technical Change Accelerate - Thomas Lindh (The Research Institute of Industrial Economics (IUI), 1991)
Leif Johansens short run macro production function is used to explore the conditions for a productivity slowdown to take place simultaneously with an accelerated technical change in production. A capacity distribution such that the supply curve is concave at the extensive margin considerably increases the likelihood of a reverse relation. Changes in price expectations may further reinforce this mechanism. Increasing costs of transferring labour to new investment is the key mechanism behind the results. The mechanism emphasizes the decisive role of past investmellt. and future price expectations in shaping the relation between technical change and productivity growth.
Keywords: A00; 330